The important of Knowledge Management and Customer Knowledge Management in enhancing organizational performance - Nor Hafizah, Abdullah; Ahmad Suffian, Mohd Zahari; Rosman, Mahmood (Medwell Journals, 2016)
In this information age, Knowledge Management (KM) and Customer Knowledge Management (CKM) have become the main competitive strategies of the organization to improve the Organizational Performance (OP). This study discusses the role of KM and CKM implementation in improving the OP. Moreover, the study also highlights the concept of KM, CKM and the related issues pertaining to this concept. This study suggests that the successful implementation of CKM is not only supported by the integration of knowledge and KM, but also need supporting from the organization. Based on the discussion, it can be concluded that the implementation of KM and CKM in the organization can play a leading role in improving the OP.